Cyprinid fishes : (Chapman & Hall, 1991)
Cyprinids rank as one of the most commercially important groups of freshwater fishes and are exploited for many purposes; as a human food source, especially in Europe and Asia; as sport fish; and as ornamental fish for ponds and aquaria. Certain species are also cultured as bait fish and several of the small cyprinids such as the zebra fish have become internationally accepted laboratory models for toxicology testing and molecular research. A thorough understanding of cyprinid health and diseases is fundamental to the successful management and exploitation of these fishes for freshwater fisheries, pisciculture and ornamental productions.